A Market Feasibility Of An Upcoming Hospital – Asahan District - Daniel Ginting; Nina Fentiana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The Regional Government of Asahan Regency has a Healthy Asahan Program committed to creating conditions in Asahan Regency that are clean, comfortable, safe and healthy for residents to live in, which is achieved through the existence of hospitals that are able to provide services according to standards. The ratio of beds to population in Asahan Regency in 2022 is 1.03. The aim of the research is to see future hospital market opportunities in an effort to help the Asahan Sehat Regional Government's Healthy Program of Asahan Regency. We used a convergent parallel mixed methods design, in which qualitative and quantitative data were collected simultaneously. This research was conducted from April 2023 to July 2023. Research data was collected from 5 hospitals in Asahan Regency (H.Abdul Manan Simatupang Hospital, Ibu Kartini Hospital, Bunda Mulia Hospital, Permata Hati Hospital, and Seger Waras Hospital), Central Bureau of Statistics and the Asahan District Health Service. Data was analyzed using SWOT and the hospital's position was determined using SWOT scoring. The SWOT analysis shows that the existence of the new hospital in Asahan Regency is in Quadrant II, meaning that the future hospital has the opportunity to develop in Asahan Regency by minimizing weaknesses. Aspects of hospital location, service/market needs, infrastructure and competitive aspects must be the main focus.